Perancangan User Experience Aplikasi Sistem Informasi Akademik berbasis Mobile menggunakan Metode Human-Centered Design (Studi Kasus: SDN Latsari I) - Sinta Karidina; Agi Putra Kharisma; Fais Al Huda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
SDN Latsari I at this time manages academic data utilize Microsoft Excel, there are several complaints from teachers regarding confusion using Microsoft Excel because of so many features provided and it takes special space and time to open desktop device use the application properly. In addition, the management of its data is limited to school storage. The distribution of student grade uses a physical report that must be returned immediately, making it difficult to monitor progress of student scores. Therefore, it requires an application that is simple and easy to manage anywhere and anytime and is connected between stakeholders and users at SDN Latsari I. This research uses human-centered design method to develop solution that focus on human perspectives into all parts of problem-solving process. The output from this study is a prototype which is a high-fidelity design. The results of evaluation using usability aspects, effectiveness of school operators gets 94.73%, teachers 96%, and students / guardians 96.66%. The efficiency aspect gets 0.209 goals/sec. Aspects of user satisfaction using single-ease questions get quantitative data on an average scale of 6.71, and qualitative data are the suggestions from users. The test results using UEQ get all excellent results.